2021
DOI: 10.1101/2021.02.04.21251165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 prevention behaviour over time in Australia: Patterns and long-term predictors from April to July 2020

Abstract: Background: In Australia in March 2020 a national public health directive required that non-essential workers stay at home, except for essential activities. These restrictions began easing in May 2020 as community transmission slowed. Purpose: This study investigated changes in COVID-19 prevention behaviours from April-July 2020, and psychosocial predictors of these behaviours. Methods: 1,843 participants in Australia completed a national COVID-19 survey in April, with monthly follow-up over four months. Prin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…From the results of the study, it was found that the level of concern of respondents regarding the COVID-19 vaccination was low at 34.4%. The results of this study are in line with research by Dodd et al (2020) conducted in Australia and showed that concerns about vaccine side effects were low at 10% [11].…”
Section: Resultssupporting
confidence: 91%
“…From the results of the study, it was found that the level of concern of respondents regarding the COVID-19 vaccination was low at 34.4%. The results of this study are in line with research by Dodd et al (2020) conducted in Australia and showed that concerns about vaccine side effects were low at 10% [11].…”
Section: Resultssupporting
confidence: 91%
“…The results in this study may have implications for the modelling of the transmission of the virus, as well as raising questions for the targeting and design of behaviour change interventions. This study adds to a small literature examining compliance across the current and previous pandemics, showing variations in behaviour across time and between groups (Ayre et al, 2021;Cowling et al, 2010;Jørgensen et al, 2021;Petherick et al, 2021;Schneider et al, 2021;van der Weerd et al, 2011;Wright & Fancourt, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we used (unbalanced) panel data from 50,000 adults from across two waves of the COVID-19 pandemic in the UK (April 2020-February 2021 to model individual trajectories of (self-reported) compliance with COVID-19 guidelines. We used latent class growth analysis to identify "typical" compliance trajectories (Herle et al, 2020), examined whether these were compatible with behavioural fatigue, and tested how compliance trajectories were related to a variety of demographic, personality trait and individual risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the findings from this study align with those from similar studies conducted during the early phase of the COVID‐19 pandemic. 20 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%